Transformation of Rules of Origin Dispute Settlement In Free Trade Agreement Scheme Through Mutual Agreement Procedure - Ardiansyah, Ardiansyah (Nurani, 2022)
Dispute resolution has been regulated in a free trade agreement (FTA) so the dispute resolution procedure should follow the dispute resolution procedure established by the FTA (das sollen). However, FTA dispute settlement procedures are not widely used to resolve disputes between importers, exporters, and state authorities related to import duty rates on imported goods in the FTA scheme. Litigation procedures in each country are the only option (das sein). Normative juridical law research methods use a statute approach to FTAs ​​and a comparative approach to dispute settlement in the field of international tax law. Research proves the weakness of FTA dispute resolution, namely the private sector and the business world as the main stakeholders in FTA schemes do not get the right to justice in disputes (access to justice) so that disputes are resolved through domestic litigation in each country. As a result, exporters and authorities of the exporting country who are not involved in the litigation process may be disadvantaged in court decisions in the importing country. Transformation of dispute resolution in FTA agreements through the mutual agreement procedure (MAP) as in international tax law (tax treaty) must be made to provide an opportunity for parties from both countries in FTA agreements, both the private sector and the competent authorities to submit objections.